Potential role of Ga-DOTATOC PET/CT in screening for pancreatic neuroendocrine tumour in patients with von Hippel-Lindau disease. - Prasad, Vikas; Tiling, Nikolaus; Denecke, Timm; Brenner, Winfried; Plöckinger, Ursula (European Journal of Nuclear Medicine & Molecular Imaging, 2016)
Purpose: Neuroendocrine tumours of the pancreas (pNET) are observed in 8 - 17 % of patients with von Hippel-Lindau disease (vHLD), and 11 - 20 % of these patients develop metastatic disease. MRI and CT have a very high resolution; however, their sensitivity and specificity for the detection of pNET amongst cystic lesions in the pancreas of vHLD patients are generally considered insufficient. In contrast, Ga-DOTATOC PET/CT demonstrates a high sensitivity for the diagnosis and staging of neuroendocrine tumours. In this study we investigated the potential role of Ga-DOTATOC PET/CT in screening of patients with vHLD. Method: Ga-DOTATOC PET/three-phase contrast-enhanced CT was performed according to guidelines in all consecutive vHLD patients between January 2012 and November 2015. All patients underwent additional MRI imaging of the abdomen, spine, and head. Chromogranin A (CgA) was determined at the time of the PET/CT examination. A lesion seen on Ga-DOTATOC PET in the pancreas was defined as positive if the uptake was visually higher than in the surrounding tissues. Lesions were quantified using maximum SUV. Results: Overall, 20 patients (8 men, 12 women; mean age 44.7 ± 11.1 years) were prospectively examined. Genetically, 12 patients had type 1 vHLD and 8 had type 2 vHLD. Ga-DOTATOC PET/CT detected more pNET than morphological imaging (CT or MRI): 11 patients (55 %; 8 type 1, 3 type 2) vs. 9 patients (45 %; 6 type 1, 3 type 2). The concentration of CgA was mildly elevated in 2 of 11 patients with pNET. The mean SUVmax of the pancreatic lesions was 18.9 ± 21.9 (range 5.0 - 65.6). Four patients (36.4 %) had multiple pNETs. The mean size of the lesions on CT and/or MRI was 10.4 ± 8.3 mm (range 4 - 38 mm), and 41.1 % were larger than 10 mm. In addition, somatostatin receptor-positive cerebellar and spinal haemangioblastomas were detected in three patients (SUVmax 2.1 - 10.1). One patient presented with a solitary somatostatin receptor-positive lymph node metastasis. pNETs were observed more frequently in vHLD type 1 than type 2 (66.7 % vs. 37.5 %, p = 0.089). None of the patients showed progressive disease during follow-up. Conclusion: In this study, Ga-DOTATOC PET detected pNETs in a higher proportion of patients with vHLD than found in previous studies with In-octreoscan, the imaging method recommended by the NCCN. We therefore suggest Ga-DOTATOC PET/CT as the more sensible screening tool.